Effects of Radiation on the Histology of the Tongue and Lip Mucosa in Rats : Preliminary Research - Sagita Yudha; Aisyah Elliyanti; Eti Yerizel; Sukri Rahman (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
The tongue and lip mucosa, as tissues with high cell proliferation rates, are highly susceptible to injury caused by ionizing radiation. This study aimed to evaluate histological changes in the tongue and lip mucosa of rats after exposure to ionizing radiation at various doses. Nine rats were used, each consisting of three rats, divided into a negative control group (K) and three treatment groups receiving radiation doses of 13 Gy (30 seconds of radiation), 15 Gy (66 seconds of radiation), and 17 Gy (110 seconds of radiation). Samples of tongue and lip mucosa tissue were harvested after 7 days and processed for histological examination using Hematoxylin and Eosin (HE) staining at 100x objective magnification. The results of this preliminary study showed that radiation at 13 Gy caused epithelial erosion, loss of filiform papillae, subepithelial bullae formation, and acute inflammatory cell infiltration on the tongue. At 15 Gy, more extensive ulceration with subepithelial edema was observed. At 17 Gy, total epithelial loss with massive subepithelial edema and vascular dilatation occurs. This preliminary study concludes that the tongue mucosa exhibits greater radiation sensitivity than the lip mucosa, with a dose-dependent progression of damage ranging from erosion to total epithelial loss.